Cool Materials and the Heat Island Effect: a bibliometric analysis - Guedes, Rodrigo Borges Nascimento; Lavorato, Marina; Pezzuto, Cláudia Cotrim (Revista Nacional de Gerenciamento de Cidades, 2021)
A current problem triggered by anthropological factors that many cities in the world face is the increase in temperature in urban centres caused by urban heat islands. There is a constant proposal for measures to reduce these effects, which can be harmful to the health and well-being of the population. The purpose of this work is to carry out a bibliometric mapping to analyse the published documents on cool materials regarding the mitigation effects of heat islands and to understand their origin and possible reasons that led to the study of this theme. From the SCOPUS database, searching for “Cool Material AND (Albedo OR Reflectance) AND Heat Island”, the scientific documents (engineering area) published between 1995 and 2021 were selected and analysed: the types of documents, their origin, the year of publication, the main authors and the journals in which they were published. Energy and Buildings and Building and Environment were the two main journals on the subject. 1995 had the first article published and coincided with the year of the first Conference of the Parties (COP1), on climate change. Through a bibliometric survey, it is possible to understand the importance of the beginning of this line of research and that climatic events can trigger interest and bring the scientific view to a certain area. However, because it is a single-base study, the research, despite bringing good information, still needs constant updates.